2012
DOI: 10.1111/bjh.12014
|View full text |Cite
|
Sign up to set email alerts
|

Cytoadherence in paediatric malaria:ABOblood group,CD36, andICAM1 expression and severePlasmodium falciparuminfection

Abstract: As a leading cause of childhood mortality worldwide, selection pressure by Plasmodium falciparum continues to shape the human genome. Severe disturbances within the microcirculation result from the adhesion of infected erythrocytes to host receptors on monocytes, platelets, and endothelium. In this prospective study, we compared expression of all major host cytoadhesion receptors among Ugandan children presenting with uncomplicated malaria (n = 1078) versus children with severe malaria (n = 855), including cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 55 publications
3
30
0
Order By: Relevance
“…These changes were associated with significant Odds ratios suggesting decreased and increased risks of eBL among individuals with O and non-O blood groups respectively. These findings are interpreted to be a reflection of decreased and increased risks of severe malaria in individuals with O and non-O blood groups respectively as previously reported in earlier studies [3,4,12,13]. Previous studies have shown that malaria was associated with immune suppression, increased EBV load and polyclonal B cell activation, all of which are important in the pathogenesis of eBL [1,7].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These changes were associated with significant Odds ratios suggesting decreased and increased risks of eBL among individuals with O and non-O blood groups respectively. These findings are interpreted to be a reflection of decreased and increased risks of severe malaria in individuals with O and non-O blood groups respectively as previously reported in earlier studies [3,4,12,13]. Previous studies have shown that malaria was associated with immune suppression, increased EBV load and polyclonal B cell activation, all of which are important in the pathogenesis of eBL [1,7].…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies have shown that malaria was associated with immune suppression, increased EBV load and polyclonal B cell activation, all of which are important in the pathogenesis of eBL [1,7]. These malaria induced immune deregulations would be greater in persons with non-O blood groups because of their vulnerability to severe malaria [3,4,12,13]. Conversely, persons with O blood group, which is associated with non-severe malaria, would incur milder malaria associated pathology because of their reduced vulnerability to severe malaria [3,4,12,14].…”
Section: Discussionmentioning
confidence: 99%
“…Between 15 October 2007 and 30 October 2009, children aged 0.6 to 10.6 years living in an area in Uganda where malaria transmission is holoendemic and presenting to the Acute Care Unit of Mulago Hospital in Kampala with fever and Plasmodium falciparum malaria were eligible for enrollment in a nested case-control study, as described previously (33,34). Briefly, children were diagnosed with uncomplicated (UM) or cerebral (CM) malaria according to World Health Organization criteria (35).…”
Section: Methodsmentioning
confidence: 99%
“…Children 6 months to 12 years of age with either uncomplicated or severe malaria were enrolled in a prospective observational study conducted at the Acute Care Unit of Mulago Hospital in Kampala, Uganda 26. Mulago Hospital is a 1,500 bed national referral center and teaching hospital of Makerere University College of Health Sciences where a previous study documented a 4.2% case-fatality rate among 23,342 children with malaria 27.…”
Section: Methodsmentioning
confidence: 99%